Depression Level and Relation with Clinical Parameters in Fibromyalgia Syndrome - Neslihan Soran,; Özlem Altındağ,; Ahmet Demirkol, (Archives of Rheumatology, 2008)
Objective: Fibromyalgia is a chronic pain syndrome characterized by widespread pain. Fibromyalgia may be frequently associated with psychiatric disorders especially depression. However, there were few studies indicating the relationship between the level of depression and disability in fibromyalgia. The aim of this study was to investigate the relationship between level of depression and clinical findings in fibromyalgia. Patients and Methods: A total of 29 patients diagnosed with fibromyalgia and 38 healthy patients were included in the study. Severity of the pain, depression level, disability and severity of disease were evaluated by Visual Analogue Scale (VAS), Hamilton Depression rating scale (HAM-D), Health Assessment Questionnaire (HAQ), Fibromyalgia ‹mpact Questionnaire (FIQ) respectively. Tender point number was determined by physical examination. Results: There were no differences between patients and controls in respect to HAQ [median (minimum-maximum) score: 1.5 (1.1-1.7) and 1.4 (1.1-1.8) respectively]. VAS, FIQ and Ham-D scores were significantly higher in patient group (p<0,001). Further, Ham-D scores were positively correlated with FIQ scores and VAS in the patient group (r=242, p = 0.04; r=296, p=0.01). Conclusion: Our results indicated that the level of depression was higher in patients and depression level was related to severity of disease. We suggest that evaluation and management of psychiatric disorders, especially depression may have additional effects in the treatment of fibromyalgia syndrome (Rheumatism 2008; 23: 1-4)